A review of the genus Leptoteratura Yamasaki, 1982 (Orthoptera: Tettigoniidae: Meconematinae) from China - Mao, Shao-Li; Shi, Fu-Ming (Zootaxa, 2007)
Keys to the subgenera of Leptoteratura, to the species of subgenus Leptoteratura from China and to all species of subgenus Rhinoteratura are presented. One new species Leptoteratura (Rhinoteratura) lamellatus Mao et Shi, sp. nov. and generic diagnosis are presented. Type specimens are deposited in Museum of Hebei University, Baoding.